Hydrolytic Stability of Aqueous Solutions of Salicin; Pharmaceutical Chemistry Journal; Vol. 54, iss. 8 - Nekhoroshev S. V.; Nekhorosheva A. V.; Sabutova A. B.; Botirov E. Kh.; Drenin A. A.; Gornikov N. V.; Slepchenko G. B. Galina Borisovna (2020, 2020)
Title screen